1993
DOI: 10.1557/jmr.1993.1226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver additions on resistance to thermal shock and delayed failure of YBa2Cu3O7−δ superconductors

Abstract: The effect of silver (Ag) addition on the resistance to thermal shock and delayed failure of YBa2Cu3O7_s superconducting wires has been evaluated. Resistance to thermal shock was evaluated by measuring the critical-current density (Jc) as a function of the number of thermal cycles for YBCO and its composites with 15 vol. % Ag additions. Composite YBCO-Ag wires show a slower decrease in Jc than does monolithic YBCO as the number of thermal cycles increases. The nature of delayed failure was studied by measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Silver is one of the few metals which can be added to 123 without degrading its superconducting properties. Many favourable properties on the addition of Ag have been reported in the literature [43][44][45][46][47]. Silver is thought to improve not only the mechanical properties like Young modulus and fracture toughness, but also is observed to reduce the gap width between the platelets [48] probably by its partial dissolution in the liquid thereby modifying the liquid phase properties below T p [49].…”
Section: Gdba 2 Cu 3 O 7 /Gd 2 Bacuo 5 +Ag Compositementioning
confidence: 99%
“…Silver is one of the few metals which can be added to 123 without degrading its superconducting properties. Many favourable properties on the addition of Ag have been reported in the literature [43][44][45][46][47]. Silver is thought to improve not only the mechanical properties like Young modulus and fracture toughness, but also is observed to reduce the gap width between the platelets [48] probably by its partial dissolution in the liquid thereby modifying the liquid phase properties below T p [49].…”
Section: Gdba 2 Cu 3 O 7 /Gd 2 Bacuo 5 +Ag Compositementioning
confidence: 99%
“…During the deposition cycles, a controlled excess of Gd material is introduced to promote Gd-rich secondary phase precipitation during the oxidation cycles. Elemental Ag was co-evaporated alongside Gd, Ba, and Cu during HTS deposition, which is known to promote YBa 2 Cu 3 O 7−d oriented growth (Matsumoto et al, 1989;Chuang et al, 1995;Clausen et al, 1996), improve mechanical properties by filling voids (although no voids were found in this study) (Singh et al, 1993;Chuang et al, 1995), increase critical current densities (Matsumoto et al, 1989;Chuang et al, 1995;Misra et al, 1995;Clausen et al, 1996), and improve thermal cycling (Singh et al, 1993). The Sm sample was not, however, doped with Ag.…”
Section: Manufacture Ofmentioning
confidence: 90%
“…Recent studies have shown that the maximum trapped field is restricted by the poor mechanical properties of bulk superconductors, and therefore their improvement is critical for the achievement of high trapped fields. It is known that Ag addition is effective in improving the mechanical properties [8,9]. The peritectic decomposition temperature of LRE-Ba-Cu-O is depressed with Ag addition, however no appreciable change in T c is observed.…”
Section: Introductionmentioning
confidence: 98%